Potential of Trachyspermum ammi (ajwain) Gel for Treatment of Facial Acne vulgaris: a Pilot Study with Skin Biophysical Profile Assessment and Red Fluorescence Photography - Ziba Talebi; Gholamreza Kord Afshari; Saman Ahmad Nasrollahi; Alireza Firooz; Maedeh Ghovvati; Aniseh Samadi; Mehrdad Karimi; Sima Kolahdooz; Mahdi Vazirian* (Iranian Society of Pharmacognosy, 2020)
Background and objectives: Acne vulgaris is one of the most common dermatologic conditions. The available anti-acne treatments are not satisfactory and safe. In this regard, searching for new treatments, especially natural materials with reasonable side effects and satisfactory effectiveness, could be promising. The aim of the present study was to explore the safety and efficacy of a topical formulation containing Trachyspermum ammi (ajwain) fruits essential oil in patients with facial acne. Methods: The essential oil of the fruits was extracted by hydrodistillation method and formulated as a 1% gel. In this open-labeled, uncontrolled clinical trial, 20 patients with mild to moderate acne received topical ajwain gel twice daily for 8 weeks. The outcomes of acne lesion count, red fluorescence parameters and biophysical skin profiles were evaluated at baseline, 4th and 8th weeks. Any adverse reaction was recorded during the study.  Results: All patients completed the study. Two months after treatment, the mean reduction in the total (8.2±3.36; P=0.000) and non-inflammatory (7.3±4.53; p=0.000) lesions was statistically significant. Furthermore, a significant reduction in the size and quantity of red fluorescence spots was also observed. Biophysical skin profile measurements revealed a significant reduction in erythema (p=0.033) and sebum (p=0.026) and a significant increase in pH (p=0.005). No serious adverse events were reported. Conclusion: The results of this pilot study provided a basis for the effectiveness of topical ajwain gel for the treatment of mild to moderate facial acne. Conducting further double blind clinical trials are necessary to confirm the efficacy and safety of the product.